(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The main principles of the HACCP system and algorithms for its development for food products are considered. The main critical control points are determined and a basic block diagram of the production of structured meat products is given. Potential risks and limit values of critical control points during product production have been identified. The expediency of using the HACCP system in the development and introduction of new products is substantiated.